Private padvragvervoer in Suid-Afrika (2014)
M.Com. (Economics) === The objective of this study was to obtain information that will enable the identification of the role, nature and magnitude of private road freight transport in the South African economy. The underlying rationale was the lack of information in this regard in South Africa. Information about private road freight transport was obtained on a sectoral basis by means of a literature analysis and an empirical investigation.